Recent Advances in Multiferroics and Magnetoelectrics Based Devices: A Review of Patents - Lekha, Chitra; Sudarsanan, Vivek; S. Nair, Swapna (Recent Patents on Materials Science, 2014)
Multiferroics and magnetoelectrics are closely correlated research areas which assume high level of research significance owing to their versatile application potential in devices like memory/storage devices, sensors/transducers, FETs, transistors etc. Extensive research has already been carried out in this particular area and numerous review articles have been published detailing their theoretical concepts, simulation of their properties, development of novel materials for device applications, lead free alternatives etc. However, most of the reviews on this topic are limited to research articles. A systematic review of recent patents in different aspects of multiferroics and magnetoelectrics will thus be a promising article which can outline the device level application of these materials in a comprehensive way. In this review article, general developments in the fabrication of novel devices based on multiferroic and magneto electric materials are discussed. Basic understanding of the existing theories in the field is also explained for non-expert readers. Pioneering research achievements published in research articles are also cited along with the vast coverage of patents.
Keywords: Magnetism